Aquatic pollution and fish reproduction : a bibliographical review - Pandey, A C (Indian Journal of Fisheries, 2011)
The present review reveals that most of the extant work on the effect of aquaticpollution on fish reproduction pertain to the changes in percentage gonadal weightand structural changes in the reproductive system in majority of the fishes studied.Effect on hormonal titres and synthesis has been worked out in only few species.From these studies, it is apparent that aquatic pollution retards the reproductiveprocesses in both sexes by impairing the gonadal development, inhibiting thematuration of spermatocytes and oocytes, delaying ovulation, breaking andclumping of yolk material in oocytes and suppressing the synthesis of gonadalsteroids via hypothalamo-hypophysial-gonadal axis. Ultrastructural studies arelacking. No fish group, other than teleosts, majority being freshwater, has beenattempted so far. Most of the extant work are confined to Channa (Ophiocephalus)punctatus, Heteropneustes fossilis, (Saccobranchus), Sarotherodon (Tilapia)mossambicus, Clarias batrachus and Colisa (Trichogaster) fasciatus.